Y90‐Ibritumomab tiuxetan (Y90‐IT) and high‐dose melphalan as conditioning regimen before autologous stem cell transplantation for elderly patients with lymphoma in relapse or resistant to chemotherapy: a feasibility trial (SAKK 37/05). Issue 4 (28th September 2016) - Voegeli, Michèle; Rondeau, Stephanie; Berardi Vilei, Simona; Lerch, Erika; Wannesson, Luciano; Pabst, Thomas; Rentschler, Jochen; Bargetzi, Mario; Jost, Lorenz; Ketterer, Nicolas; Bischof Delaloye, Angelika; Ghielmini, Michele
Abstract: Standard conditioning regimens for autologous stem cell transplantation (ASCT) are often not tolerated by elderly patients, on one hand. Single high‐dose melphalan, on the other hand, has been shown to be safe and active as a pretransplant preparative regimen in elderly patients. Y 90 ‐Ibritumomab tiuxetan (Y 90 ‐IT) is well tolerated and feasible in the transplantation setting. We therefore investigated the combination of high‐dose melphalan and Y 90 ‐IT as a conditioning regimen for patients ≥65 years of age. Patients with relapsed or resistant CD20‐positive lymphoma in remission after salvage chemotherapy could be enrolled. High‐dose therapy consisted of standard dose Y 90 ‐IT (0.4‐mCi/kg body weight) followed by melphalan at escalating doses (100, 140, 170 and 200 mg/m 2 ) and ASCT. The primary objective was to identify the maximum tolerated dose; secondary end points were complete response (CR) rate 100 days after transplantation and toxicity. Twenty patients (median age 72 years) were included. No DLT occurred at any dose level. Thirteen patients completed the treatment, 11 were evaluable for response. Seven patients did not complete treatment because of mobilization failure (n = 3), progressive disease (n = 2), worsening of cardiac function (n = 1), and grade 3 dyspnea (n = 1). Seven patients achieved a CR/complete remission/unconfirmed (CRu) and 2 had stable disease. Five out of 7 responding patients were still alive more than 3 years after transplantation. The 2 patients with SD had a long‐term survival of 3 and 5 years, respectively. Nonhematological grade 3 or higher treatment related adverse events (AEs) were infection (n = 6), including 2 cases of febrile neutropenia, diarrhea (n = 3), mucositis, anorexia, viral hepatitis, hypokalemia, dehydration, and multiorgan failure (n = 1 for each). The combination of Y 90 ‐IT and high‐dose melphalan is feasible before ASCT for elderly patients, with promising activity and manageable toxicity.